Directions of integration of higher education: the choice of Belarus - Kuish, Alexander L. (Journal of the Belarusian State University. Sociology, 2019)
The work is devoted to the problem of choosing directions of integration of higher education of the Republic of Belarus into the world educational systems. The idea of multi-vector approach in relation to educational integration processes (in the European, Eurasian and Asian directions) is stated with the justification of the priority for today of the European direction. The conditions, principles and ways of this kind of integration are analyzed.
Keywords: higher education; European Higher Education Area; Eurasian Economic Union; Bologna process